2022
DOI: 10.29133/yyutbd.1136973
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Inorganic Fertilizer and Biofertilizer Applications on Some Quality and Biochemical Properties of Safflower (Carthamus tinctorius L.)

Abstract: This study was carried out in irrigated conditions during the summer growing season of 2020 and 2021 to determine the effects of biofertilizer applications and inorganic fertilization on some quality and biochemicals properties of safflower (Carthamus tinctorius L.) in Van ecological conditions. The experiment was set up as a randomized block design in 3 replicates at the Faculty of Agriculture, Van Yüzüncü Yıl University. The mixture of five different biofertilizers (Frateuria aurantia (B1), Bacillus megateri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Mir et al (2017) the low light intensity state showed higher flavonoid productivity (2.5 mg g -1 dry weight) when compared to the high sunlight intensity condition in A. amygdalina plants. However, Yolci and Tunçtürk (2022) reported was the total content of flavonoids and antioxidant activity, with the best results obtained in the NP0 treatment (without nitrogen and phosphorus fertilizers) on safflower (Carthamus tinctorius ). This is due to differences in plant species, geography, and environmental factors that cause differences in total flavonoid content and antioxidant activity.…”
Section: Discussionmentioning
confidence: 99%
“…Mir et al (2017) the low light intensity state showed higher flavonoid productivity (2.5 mg g -1 dry weight) when compared to the high sunlight intensity condition in A. amygdalina plants. However, Yolci and Tunçtürk (2022) reported was the total content of flavonoids and antioxidant activity, with the best results obtained in the NP0 treatment (without nitrogen and phosphorus fertilizers) on safflower (Carthamus tinctorius ). This is due to differences in plant species, geography, and environmental factors that cause differences in total flavonoid content and antioxidant activity.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, droughtinduced stress is defined as the lack of moisture required for normal plant growth and life cycle completion (Mousavi-Avval et al, 2011), which causes 55% of crop losses in the entire of world (Bray et al, 2000) and affects nearly every aspect of the plant such as morphology, physiology and metabolism (Jabereldar et al, 2017;FAO, 2019). Therefore, it is important to choose an alternative crop in place of plants with high water needs and compatible with the stress of drought (Yolci and Tunçtürk, 2022).…”
Section: Introductionmentioning
confidence: 99%